2010
DOI: 10.1143/jjap.49.04dc07
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Effect of Channel Doping Concentration on Random Telegraph Signal Noise

Abstract: Four groups of grain sizes of LiF:Mg,Cu,P material were chosen for the experiment. The influences of the grain size on the photon energy response and dose response have been examined in the intewal of 28-1250 keV and the dose range 0.190 Gy of ' %o y-rays. The experimental results show that both the energy response and the dose response are grain size dependent. A possible correlation seems to exist between the energy response v(E) and the dose response f ( D ) . A brief discussion is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…On the other hand, random telegraph noise (RTN) is another issue of the fluctuation of transistor characteristics [9], and the suppression of the RTN effect is essential for future scaled MOSFETs. It is reported that the amplitude of RTN depends on channel doping concentration [10]. These results suggest that, if the dopant atoms are removed from the channel, not only Vth variability but DIBL variability, COV variability, and RTN amplitude will be suppressed.…”
Section: Introductionmentioning
confidence: 86%
“…On the other hand, random telegraph noise (RTN) is another issue of the fluctuation of transistor characteristics [9], and the suppression of the RTN effect is essential for future scaled MOSFETs. It is reported that the amplitude of RTN depends on channel doping concentration [10]. These results suggest that, if the dopant atoms are removed from the channel, not only Vth variability but DIBL variability, COV variability, and RTN amplitude will be suppressed.…”
Section: Introductionmentioning
confidence: 86%
“…This means that channel percolation increases the probability of RTN generation. Figure 9 shows the Gumbel plot of the RTN amplitude for MOSFETs with varying channel doping [51]. The channel percolation is accelerated by increasing channel doping concentration [46][47][48].…”
Section: Statistical Evaluation Of Rtn Characteristicsmentioning
confidence: 99%
“…This figure shows that the probability of the number of MOSFETs with large amplitude increases with doping concentration. RTN is increased by channel Figure 9 shows the Gumbel plot of the RTN amplitude for MOSFETs with varying channel doping [51]. The channel percolation is accelerated by increasing channel doping concentration [46][47][48].…”
Section: Statistical Evaluation Of Rtn Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To fully understand the RTN, it is necessary to characterize the statistical distributions, emission-capture time constants, activation energies, noise power spectra densities, physical locations, and the relations to detailed fabrication processes. In spite of being studied in the past several decades [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], many RTN-related issues still remain as active research topics due to the nature of its complexity.…”
Section: Introductionmentioning
confidence: 99%